2020
DOI: 10.1088/1742-6596/1484/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Pulse laser ablated growth of Au-Ag nanocolloids: Basic insight on physiochemical attributes

Abstract: Despite considerable research the evidence around the wide applications in the nanomedicine and nanophotonic area of gold-silver (Au–Ag) nanocolloids remains equivocal and under exploration. Due to their physical properties, enhanced permeability, high fluorescent, surface area to volume ratio, retention effect, localized surface plasmon resonance (LSPR) and controlled perfusion of drugs, made Au–Ag nanoparticles is over interested. Hence, we produced Au–Ag nanocolloids using nanosecond pulse laser ablation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Also, [20] used the K-mean clustering, but this time with the Zack algorithm; unfortunately, the authors used only seven images to evaluate the proposed method and got an overall segmentation accuracy of 96.60. Similarly, [21][22][23][24][25] proposed an ALL segmentation approach based on hybrid histogram-based soft covering rough k-means clustering. In addition, they used several features extracted from 350 images derived from the Gray Level Cooccurrence matrix and got an overall segmentation accuracy above 90%.…”
Section: Related Workmentioning
confidence: 99%
“…Also, [20] used the K-mean clustering, but this time with the Zack algorithm; unfortunately, the authors used only seven images to evaluate the proposed method and got an overall segmentation accuracy of 96.60. Similarly, [21][22][23][24][25] proposed an ALL segmentation approach based on hybrid histogram-based soft covering rough k-means clustering. In addition, they used several features extracted from 350 images derived from the Gray Level Cooccurrence matrix and got an overall segmentation accuracy above 90%.…”
Section: Related Workmentioning
confidence: 99%
“…Because they rely on constant values to assign DNA base pairs, most existing approaches cannot account for variations in the structure of the DNA sequence. Since different mappings can produce different structural features, it was decided that the choice subject-specific in terms of numerical mapping [31][32][33][34][35].…”
Section: Symboli -To-numberi Mapping Using Dna Sequencei Analysisimentioning
confidence: 99%
“…The result of comparisons of the proposed encryption system with several existing classical methods of showed that the proposed algorithm has smaller correlation coefficients compared with them. Ref [24] 0.00014 -0.00368 -0.02298 Ref [25] 0.0016 -0.0088 -0.0254…”
Section: B3 = 𝑟𝑜𝑢𝑛𝑑[255 * B2 − Min 𝑚𝑎𝑥 − 𝑚𝑖𝑛 ]mentioning
confidence: 99%